CAPTURING INDIGENOUS KNOWLEDGE ON MEDICINAL PLANTS USE: CASE STUDY OF SELECTED COMMUNITIES IN OLD OYO NATIONAL PARK, NIGERIA - Oladeji, S.O.; Agbelusi, E.A. (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Understanding the intricate link between humans and the plants use is needed to address some of to-day’s socio-economic and health challenges.Materials and Methods: The study focused on plants that have high cultural and medicinal values for the host communities of Old Oyo National Park, Nigeria. Local Knowledge was captured through focus group discussions with herbal vendors, interviews with herbalists as key informants and through field observations. Snowball sampling technique was used in selecting the key informants. Participants selected for the Focus Group Discussion varies with the number of herbal vendors encountered in each commercial market.Results: In total, 78 medicinal plant species belonging to 39 families including 47 trees, 8 shrubs and 23 herbaceous plants were documented. Forty ailments categorized into thirty one treatments and prevention methods were discovered. Kigellia africana, Cassia spp and Alstonia boonei were used for treating common ailments like malaria, dysentery and gonorrhea. Sources of collecting the medicinal plant species and their mode of administration were different.Conclusion: The research outcome will contribute to advancement of traditional medicine, resource efficiency and development of new enterprise among the locals. Comprehensive quantitative study of social- economic importance of the medicinal plants is recommended.